Створення системи контролю версій 3D моделей - Рожко, Д. В. (ХНУРЕ, 2023)
In recent years, the demand for 3D models has been increasing in various fields of activity, such as the entertainment industry, architecture, medicine, and others. However, due to the increase in size and complexity of 3D models, there is a need for effective version control of these files. At the same time, a number of ready-made version control solutions for ordinary or even only text files such as Git or SVN is not sufficient, because it does not correspond to the specifics of 3D files and therefore loses in functionality This work is devoted to the development of a version control system for 3D models.